Factors contributes towards student dishonesty during teaching & learning through Open Distance Learning (ODL): a case study among UiTM Seremban 3 students / Anis Khalyshah Mukhlis and Maizatul Nazirah Osman - Mukhlis, Anis Khalyshah; Osman, Maizatul Nazirah (2022)
According to (Donald L. McCabe, 2016)’s surveys of cheating among college students, academic dishonesty is both common and growing. The issue arises when student was dishonest in doing their assessment and examination. This research study aims to find out the factors contributes towards student dishonesty during teaching & learning through Open Distance Learning (ODL) Among UiTM Seremban 3 Students. Objective of this research is to see if there is any interrelation between Dependent Variable which is factor student’s dishonesty during ODL and Independent variable which are peer pressure, students’ academic performance and environment during teaching and learning. Besides that, this is quantitative research method. The data collection is done through standardize questionnaire distribution to UiTM Seremban 3’s last semester student from FSPPP. The questionnaire was distributed through Google Form online and there are 355 participations responded. Based on the study finding shows that there was significant relationship between DV and IVs. Finding also shows that the hypothesis is accepted, and null hypothesis was rejected. There is stated about research limitation and future recommendation while conducting this study so that other researcher who want to do this research can used.